A nightmare on Elm Street 3, Dream warriors ; A nightmare on Elm Street 4, The dream master [videorecording (DVD)] - Englund, Robert, 1947-; Langenkamp, Heather, 1964-; Wasson, Craig; Arquette, Patricia, 1968-; Fishburne, Laurence, III, 1961-; Knight, Tuesday; Eastman, Rodney, 1967- (New Line Home Video, 2017)
A nightmare on Elm Street 3 : Dream warriors: The last of the Elm Street kids are now at a psychiatric ward, where demented killer Freddy Krueger haunts their dreams with unspeakable horrors. Their only hope is dream researcher and fellow survivor Nancy Thompson, who helps them battle the supernatural psycho on his own hellish turf--